Utilization of Kinemaster Application in Making Natural Science Teaching Media - Aji, Arif Rahmatul; Azizah, Azizah; Almimbar, Alvi Huda (Journal of Social Science Utilizing Technology, 2023)
Background. In this globalization era, we as a teacher must be able to create a renewal in learning. As we know that at this time there are still many schools that still use a learning media system that is far from the influence of globalization, meaning that they still use old-fashioned learning media. Therefore, in this article we submit some utilization of an application, one of which is called Kinemaster, which can create simpler and more modern learning media. Purpose. The purpose of this study is to use the kinemaster application as a learning medium so that learning is more interesting, colourful and makes students happy in natural science lessons. Method. Sampling itself uses the purposive sampling method, the analysis is carried out descriptively qualitatively based on the data that has been obtained. Results. The result of this research is that the kinemaster application is very useful as a medium for learning natural science because it makes students more interested and enthusiastic in learning. Conclusion. It can be concluded that in this era of globalization everything uses an online system and everything uses a sophisticated science system and is also simple and modern. In this world of education, everything uses a sophisticated system so that we must be able to follow it so that our education system becomes modern and more interesting and clear. In this communication information technology we convey the use of the kine master application and also how to use the application from start to finish so that we can make good and clear learning media.